Women and Intangible Cultural Heritage in Tunisia: Safeguarding, Transmission, and Valorization - Ismahen BEN BARKA (Turath, 2024)
Actively participating in the safeguarding of intangible cultural heritage (ICH), women have always played an essential role in the preservation and transmission of this heritage as holders and practitioners of knowledge, skills as well as social and ritual practices. Their intervention in the field takes different forms: technical, artistic, economic, cultural and social. Their participation in the development of application files for the inscription of ICH elements on the UNESCO lists is central; they contribute to the promotion of this heritage at the national and international level.